IMPROVING THE STOCK MARKET INFRASTRUCTURE IN CONDITIONS OF ECONOMY MODERNIZATION - Ravshanjon Ismoilov; Bahriddinov Jahongirbek; Khalilov Abdulaziz Abdurashidovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article describes the economic essence of the stock market infrastructure and the main directions of its formation, the scientific and theoretical basis. The foreign experience of the stock market infrastructure and stock exchanges has been studied, and opportunities for their application to the stock market of Uzbekistan have been identified. Analysis of the institutional, technical, and functional bases of the stock market, and the economic situation in the stock market of the Republic of Uzbekistan. Factors influencing the development of stock market infrastructure were systematized and analyzes were performed on the autoregressive distributed lag ARDL model based on the factors influencing the stock market infrastructure (UCI) and their complex econometric methods.